Penetapan Batas Nagari Berdasarkan Aspek Teknis dan Non-Teknis (Studi Kasus: Nagari Pasir Binjai, Kecamatan Silaut, Kabupaten Pesisir Selatan, Sumatera Barat) - Delvi Yanti; Eri Gas Ekaputra; Eri Stiyanto (Warta Pengabdian Andalas, 2022)
The affirmation of village boundaries is the process of determining the coordinates of the boundaries, which can be carried out using cartometric methods and surveys in the field. It is outlined as a boundary map for village boundaries coordinate points as agreed. The determination of affirmation generally consists of three stages: collecting and researching boundary documents, determining a base map, and making a cartometric map of village boundaries. This activity aimed to determine boundary segments, objects, cartometric points, and artificial pillars for determining and confirming the boundaries of Pasir Binjai Village, Silaut District, and Pesisir Selatan Regency. The results of this activity were 1) Pasir Binjai Village has five boundary segments, all segments bordering the border villages within one administrative area of ​​the Silaut District government; 2) Natural boundaries, namely mark village boundary objects: river flow or middle of the river, middle of drainage or ditch, a centre of the road, and some are found on community plantation land; 3) the total number of cartometric points as a reference and the village boundary nodes are 15 points; 4) the number of pillars made for the artificial marking of the village boundaries are six pillars, there are four boundary pillars which are the primary boundary reference pillars which are not located right on the boundary line, and two boundary pillars are the main boundary pillars which are located right on the boundary line.